(untitled) (Scientific journal of the Fergana State University, 2026)
A method for synthesizing a new generation of aromatic acetylenic alcohols by alkynylation of benzaldehyde and its various derivatives containing fluorine, chlorine, bromine, oxygen, sulfur, and nitrogen atoms in their molecules with cyclopropylethene in a catalytic system prepared on the basis of ethyl magnesium chloride, 2-(dibutylamino)-1-phenylpropanol-1, and trifluoroethanol has been studied. The nature of heteroatoms in the molecules of the selected aldehydes, the effect of the catalyst and solvents, reaction time, and temperature on the yield of the products have been systematically studied. The direction, stages, and mechanisms of the alkynylation reaction have been proposed. The composition, purity, and structure of the synthesized compounds have been proven by modern physicochemical methods of study.